ANALISIS PENGARUH KINERJA PERBANKAN TERHADAP HARGA SAHAM (STUDI EMPIRIS PADA INDUSTRI PERBANKAN YANG TERDAFTAR DIBURSA EFEK INDONESIA PADA TAHUN 2012 – 2015) - Eric Alfretdo; Fakhruddin Nasution (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2021)
This study was conducted to Analyze the Influence of CAR, NIM, LDR, NPL and BOPO to Stock Prices in the banking industrial were listed on Indonesia Stock Exchange in the period 2012-2015. The sampling technique used was purposive sampling method to obtain 20 banking companies. This study uses the hypothesis test analysis model of multiple linear regression analysis (Multiple Linear Regression). The results of this study showed that the CAR dosen’t have an effect to Stock Prices. While LDR and NIM have a positive effect to stock prices. NPL and BOPO has a negative effect to Stock Prices.